2020
DOI: 10.1007/s10950-019-09897-0
|View full text |Cite
|
Sign up to set email alerts
|

A database of damaging small-to-medium magnitude earthquakes

Abstract: Interest in small-to-medium magnitude earthquakes and their potential consequences has increased significantly in recent years, mostly due to the occurrence of some unusually damaging small events, the development of seismic risk assessment methodologies for existing building stock, and the recognition of the potential risk of induced seismicity. As part of a clear ongoing effort of the earthquake engineering community to develop knowledge on the risk posed by smaller events, a global database of earthquakes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…This being the case, global observations of earthquake damage (e.g. Nievas et al, 2020a) can provide a basis for calibrating magnitude thresholds, provided certain assumptions are made regarding the completeness of reporting for damaging events (Nievas et al 2020b) and that the exposed building stock is analogous to that affected by the earthquakes for which damage was reported. However, a critical question is whether the red-light threshold of a TLS should be fixed at the target risk level, or whether it is necessary to set the red light at a lower threshold if the risk target is to be achieved.…”
Section: Tlss As Seismic Risk Mitigation Toolsmentioning
confidence: 99%
“…This being the case, global observations of earthquake damage (e.g. Nievas et al, 2020a) can provide a basis for calibrating magnitude thresholds, provided certain assumptions are made regarding the completeness of reporting for damaging events (Nievas et al 2020b) and that the exposed building stock is analogous to that affected by the earthquakes for which damage was reported. However, a critical question is whether the red-light threshold of a TLS should be fixed at the target risk level, or whether it is necessary to set the red light at a lower threshold if the risk target is to be achieved.…”
Section: Tlss As Seismic Risk Mitigation Toolsmentioning
confidence: 99%
“…In seismically active regions, even though M w = 4.0 earthquakes can be locally damaging (Nappi et al, 2021), current hazard is associated with the upper part of this magnitude range. In western Europe, M w = 4.0 to 5.0 shallow earthquakes represent the most probable current source of seismic risks, which is currently enhanced by the increase of induced seismicity by underground energetic resources (Grigoli et al, 2017;Nievas et al, 2020). In western Europe, the potential for destruction of shallow earthquakes is exemplified by the damaging impact of the 11 May 2011 Lorca (Spain, M w = 5.1; Association Française de gĂ©nie Parasismique, 2011), 16 August 2012 Huizinge (The Netherlands, M w = 3.6; Dost and Kraaijpoel, 2013) and 11 November 2019 Le Teil (France, M w = 4.9; Schlupp et al, 2021) earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Since seismic risk is a combination of seismic hazard, exposure and structures' vulnerability, and although strong earthquakes are not expected or less frequent, if buildings are not properly detailed and designed to withstand seismic loads, high losses due to small-to-moderate events may be expected. For instance, Nievas et al [3] present an extensive database of events worldwide with M from 4.0 to 5.5 for which damage and/or casualties have been reported. It also has to be highlighted damaging events that have occurred in Brazil, e.g., the JoĂŁo Câmara earthquake in Rio Grande do Norte state and the Itacarambi earthquake in Minas Gerais state ([2], Takeya et al [4]); the latter causing the first reported fatal victim due to earthquakes in Brazil.…”
Section: Introductionmentioning
confidence: 99%